Konstruksi Reputasi dan Responsivitas Instansi Pemerintah Melalui Media Sosial pada Situasi Pandemi Covid-19 di Indonesia (Analisis Wacana Pada Laman Facebook Direktorat Jenderal Perbendaharaan Kementerian Keuangan RI) - Muhammad Nur (Direktorat Jenderal Perbendaharaan, Kementerian Keuangan, 2020)
Government agencies are required to continue to work and provide optimal and responsive public services to various issues and conditions. Preaching on social media can be a medium for government agencies to construct certain discourses, such as a responsive attitude to the current emergency situations. DGT as a government agency under the Ministry of Finance of the Republic of Indonesia responsible for managing the State Budget has a business continuity plan (BCP) that is responsive to various situations that occur. This article aims to find and explain the news construction process in the Facebook social media account of DJPb which shows the responsiveness of DJPb in the Covid-19 pandemic situation in Indonesia. This study uses Teun A. Van Dijk's discourse analysis (DA) method to find textual components (news schemes) of the news and texts on DJPb’s Facebook page. The results showed that there was a reputation and responsiveness construction process in the form of discourse produced in the news on DJPb's Facebook social media account during the Covid-19 pandemic situation in Indonesia. DJPb’s responsiveness is important and very necessary to ensure that public services related to disbursement of APBN such as employee salaries, BOS funds, UMi credit, etc. including APBN funds for handling in emergency situations such as the Covid-19 pandemic can continue to run well to support the implementation of government’s programs.